Natural Retinol Analogs Potentiate the Effects of Retinal on Aged and Photodamaged Skin: Results from In Vitro to Clinical Studies - Anthony Brown; Marta Furmanczyk; David Ramos; Adrià Ribes; Laia Pons; Javier Bustos; Antonio R. Fernández de Henestrosa; Corinne Granger; Eric Jourdan (Dermatology and Therapy, 2023)
Abstract Introduction Plants are a source of natural ingredients with retinol-like properties that can deliver anti-aging benefits without the side effects typically associated with retinoid use. We hypothesized that by combining two such analogs, bakuchiol (BAK) and Vigna aconitifolia extract (VAE), with the potent retinoid retinal (RAL), the anti-photoaging potential of RAL could be enhanced without compromising its skin irritation profile. The purpose of this study was to demonstrate that BAK and VAE potentiate the anti-photoaging activity of RAL. Methods Gene expression profiling of full-thickness reconstructed skin was first used to examine the impact of BAK or VAE in combination with RAL on skin biology. Next, the irritative potential of this combination, and its capacity to reverse key signs of photoaging in an ex vivo model was assessed. Finally, a proof-of-concept open label clinical study was performed to evaluate the anti-photoaging capacity and skin compatibility of a cosmetic formulation (tri-retinoid complex; 3RC) containing this complex in combination with other well characterized anti-photoaging ingredients. Results In vitro profiling suggested that combining 0.1% RAL with BAK or VAE potentiates the effect of RAL on keratinocyte differentiation and skin barrier function without affecting its skin irritation profile. When formulated with other anti-photoaging ingredients, such as niacinamide and melatonin, 3RC reversed ultraviolet radiation-induced deficits in structural components of the dermal extracellular matrix, including hyaluronic acid and collagen. In vivo, it led to a reversal of clinical signs of age and photodamage, with statistically significant improvement to skin firmness (+5.6%), skin elasticity (+13.9%), wrinkle count (−43.2%), and skin tone homogeneity (+7.0%), observed within 28 days of once nightly use. Notably, the number of crow’s feet wrinkles was reduced in 100% of subjects. Furthermore, 3RC was very well tolerated. Conclusion These data suggest that 3RC is a highly effective and well-tolerated treatment for photoaging.